PENGARUH MOTIVASI BERPRESTASI DAN FASILITAS BELAJAR TERHADAP HASIL BELAJAR MATA PELAJARAN EKONOMI KELAS XI DI MA FATHUSSALAFI MANGARAN SITUBONDO TAHUN PELAJARAN 2017/2018 - Nursalam Nursalam (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2017)
This study aims to determine the influence of achievement motivation and learning facilities on the learning outcomes of economy class XI subjects in MA Fathussalafi mangaran situbondo academic year 2017/2018. Respondents in this study students class XI in MA Fathussalafi mangaran situbondo academic year 2017/2018 amounted to 30 learners drawn from 84peserta students. Sampling using technique proportional radom sampling. This research is an ExPost Facto research where the research only examines cause and effect relationships that are not manipulated or treated by the researcher. Data collection instruments using documentation, interviews, questionnaires were analyzed using the correlation of Product Moment Statistics. Achievement motivation data obtained from questionnaires given to students amounted to 10 questions. The result of the questionnaire shows the highest score = 26 and the lowest score = 19. The study facility data is obtained from the questionnaire given to the learners amounted to 10 questions. The results of the questionnaire revealed the highest score = 24 and the lowest score 18. While the learning result data obtained from the documentation of daily test value of learners and the result is known the highest value = 90 and the lowest score 70. Known major hypothesis test r-count value of 0,665, after dikskultasikan with r-table value, the value of r-table <r-count is 0.361. The working hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. Testing of minor hypothesis X₁ (achievement motivation) to Y known value of r-count equal to 0,444, after consultation with r-table, value r-table <r-count that is equal to 0,361. The hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. Testing the minor hypothesis X₂ (learning failures) to Y is known r-count value of 0,405, after consultation with r-table, the value of r-table <r-count is 0,361. The working hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. So it can be concluded "there is influence of achievement motivation and learning facilities to the learning result of economy class XI class in MA Fathussalafi mangaran situbondo year 2017/2018".